2018
DOI: 10.3389/fmars.2018.00146
|View full text |Cite
|
Sign up to set email alerts
|

Optical Modeling of Spectral Backscattering and Remote Sensing Reflectance From Emiliania huxleyi Blooms

Abstract: In this study we develop an analytical model for spectral backscattering and ocean color remote sensing of blooms of the calcifying phytoplankton species Emiliania huxleyi. Blooms of this coccolithophore species are ubiquitous and particularly intense in temperate and subpolar ocean waters. We first present significant improvements to our previous analytical light backscattering model for E. huxleyi coccoliths and coccospheres by accounting for the elliptical shape of coccoliths and the multi-layered coccosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Higher R rs values are associated with the lower salinity of the Fraser River plume and estuarine waters (Loos and Costa, 2010;Phillips and Costa, 2017;Travers-Smith et al, 2021). For Group 2, the R rs spectra were well within the ranges observed by Moore et al (2012), Neukermans andFournier (2018), andCazzaniga et al (2021) for waters under coccolithophore bloom conditions. Specifically, Cazzaniga et al (2021) have shown high values (R rs (550) ≈ 0.03 sr −1 ) for the peak of a coccolithophore bloom, intermediate values (R rs (550) ≈ 0.02 sr −1 ) for receding bloom conditions, and low values (R rs (550) <0.01 sr −1 ) for the start and the end of bloom.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Higher R rs values are associated with the lower salinity of the Fraser River plume and estuarine waters (Loos and Costa, 2010;Phillips and Costa, 2017;Travers-Smith et al, 2021). For Group 2, the R rs spectra were well within the ranges observed by Moore et al (2012), Neukermans andFournier (2018), andCazzaniga et al (2021) for waters under coccolithophore bloom conditions. Specifically, Cazzaniga et al (2021) have shown high values (R rs (550) ≈ 0.03 sr −1 ) for the peak of a coccolithophore bloom, intermediate values (R rs (550) ≈ 0.02 sr −1 ) for receding bloom conditions, and low values (R rs (550) <0.01 sr −1 ) for the start and the end of bloom.…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, our spectra showed R rs (560) >R rs (500) likely representing the start of the bloom (water types 11 and 12; Figure 10). Other spectra showed an increase at R rs (500) (water types 8, 9, and 10), probably associated with a high concentration of detached coccoliths indicative of receding bloom conditions (Neukermans and Fournier, 2018;Cazzaniga et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Thresholds for b bp /[Chl-a] ranged from 0.0063 m 2 mg −1 in the North Atlantic subpolar gyre to 0.0078 m 2 mg −1 in the Indian sector of the Southern Ocean (Table 1). Regional differences in b bp /[Chl-a] thresholds can be expected owing to differences in backscattering properties of coccolithophore blooms (e.g., the ratio of free to attached coccoliths, Balch et al, 1999, or the morphotype of coccoliths, Neukermans & Fournier, 2018), in regional variability in background b bp associated with nonalgal material (Bellacicco et al, 2019;Zhang et al, 2020), or in phytoplankton community composition and physiology (Barbieux et al, 2018;Cetinić et al, 2015). Table 1, the method successfully identified nearly three-quarter of coccolithophore bloom cases in all temperate and subpolar regions except in the Indian sector of the Southern Ocean, and greatly differentiated bloom from non-bloom cases as illustrated by high values of specificity ( Table 1)…”
Section: Toward a Global Detection Of Coccolithophore Blooms With Bgcmentioning
confidence: 99%
“…Recently, Twardowski et al (2012), Zhang et al (2012Zhang et al ( , 2013Zhang et al ( , 2014b, Zhang and Gray (2015), and Xu G. et al (2017) have started addressing the first issue by incorporating non-spherical (i.e., hexahedral) shapes for marine particulates in their retrieval studies of scattering functions. Other efforts to account for particle non-sphericity in RT simulations of underwater light are described by Gordon et al (2009) and Gordon (2011) for the scattering properties of detached coccoliths, by Zhai et al (2013) and Bi and Yang (2015) for the scattering properties of whole coccolithophores, and by Fournier and Neukermans (2017) and Neukermans and Fournier (2018) for the scattering properties of both detached coccoliths and whole coccolithophores. In addition, Organelli et al (2018) started using coated spheres in RT computations to force closure with underwater light particulate backscattering and attenuation measurements, whereas Poulin et al (2018) compared the performance of coated spheres and hexahedral shapes in closure studies of phytoplankton cultures.…”
Section: Particulate Scattering Heritage Studies: Particulate Scattermentioning
confidence: 99%